Reliability centered condition-based maintenance of zinc oxide lightning arresters: concept, process and case study - Yang, Fan; Han, Rui; Zheng, Yu; Jiang, Peng; Wang, Wenhao; Dong, Xuzhu (Frontiers in Energy Research, 2024)
Introduction: The reliability of power equipment is the foundation for maintaining the reliability of the power grid. As a core device for limiting overvoltage in the power grid, lightning arresters have received widespread attention, and ensuring their reliability is crucial. Methods: To improve the reliability of zinc oxide surge arresters in the power system, the fault characteristics and health assessment methods of zinc oxide surge arresters were studied using reliability centered condition-based maintenance(RCCM). Firstly, the fault characteristic of zinc oxide lightning arresters in operation over years were collected and analyzed from different aspects. Then the effective state quantities corresponding to different types of defects and their detection methods were proposed. The health status evaluation model for zinc oxide lightning arrester was established, and the effectiveness of the evaluation model was verified through fault cases. Results and Discussion: It shows that the proposed state quantities and RCCM method are suitable for the actual operation and maintenance of zinc oxide lightning arresters. It can reduce the workload and improve the efficiency of existing operation and maintenance of lightning arresters.